The effects of an oral Taurine dose and supplementation period on endurance exercise performance in humans: A meta-analysis - Waldron, M.; Patterson, S. D.; Tallent, J.; Jeffries, O. (Sports Medicine, 2018)
Background: Taurine is central to many physiological processes, some of which are augmented by exogenous supply and have the potential to facilitate endurance performance; however, its independent effects on performance have not been systematically analysed. Objective: To evaluate the effects of isolated oral taurine ingestion on endurance performance and to assess the contribution of (1) the dose and (2) the supplementation period to the ergogenic effect. Methods: A search was performed using various databases in September 2017. The studies were screened using search criteria for eligibility. Ten peer-reviewed articles were identified for inclusion. A sub-analysis of time-to-exhaustion (TTE) trials (n = 7) was also performed. The effects of (1) dose and (2) the acute (single dose) or chronic (> 1 day) supplementation periods were assessed using meta-regression. The doses of taurine ranged from 1 to 6 g/day and were provided in single doses and for up to 2 weeks among a range of subjects. Results: Taurine ingestion improved overall endurance performance (Hedges` g = 0.40, 95% CI 0.12-0.67, P = 0.004), which was similar in TTE trials (Hedges` g = 0.43, 95% CI 0.12-0.75, P = 0.007). There were no differences between acute or chronic supplementation for the full sample (P = 0.897) or the TTE group (P = 0.896). The dose of taurine did not moderate its effect on endurance performance (P > 0.05). Conclusion: Human endurance performance can be improved by orally ingesting a single dose of taurine in varying amounts (1-6 g).